Investigation of factors influencing the formation of the middle class on the territory of regions of Capital socio-geographical area - Перегуда, Юлія (Human Geography Journal, 2017)
The article stated that to determine the specifics of a middle class it is necessary to apply economic and mathematical methods allowing one to display a certain proportion and sometimes qualitative patterns of distribution of different forms and types of settlement and problems that are investigated. The key components of each factor can be determined based on the analysis of factor analysis and the indicators playing a major role in shaping sets of factors can be shown based on a factor variance. The spatial organization of society in this research study has been noted to have a multi-level character, because it is going to cover the territory within the regions and the accommodation of diverse population on it will include spatial distribution of various types of economic activity and economic indicators. In this study, the special attention has been paid to economic poverty to determine the boundaries of the middle class, and conduction of more accurate inequality of economic indicators in the regions. The regional specifics of the Capital socio-geographical area has been conducted through socio-geographical approach aimed at disclosing the middle class. Based on statistical data systematization, the analysis has been conducted due to the matrix factorization of selected indicators intercorrelation. It has been noted that the study of the middle class from the standpoint of social geography as spatially conditioned phenomenon requires the formulation of methodological regulations, it defines procedures for research highlighting the main stages, and it studies the techniques and methods of forming the system of scientific research to further disclosure issues.